FERMENTASI NATA DARI SARI BUAH KURMA (Phoenix dactylifera) TERHADAP BEBERAPA VARIASI KONSENTRASI STARTER Acetobacter xylinum - Rumi, Amelia (Jurnal Ilmiah As-Syifaa, 2016)
It has conducted research on the utilization of kurma juice to several concentration variant starter Acetobacter xylinum, by measuring the thickness, weight, moisture content, ash content, and crude fiber content. Date palm juice which was added glacial acetic acid, potassium dihidrogen phosphate 600 mg, magnesium sulphate 600 mg, sugar 48 gram, and 6 gram of urea and incorporated into several containers of 100 ml and varied the volume of the starter 5 %, 10 %, and 20 % of 14x24 hours fermented in 37 Â temperature. Results showed the concentration of 5 % was obtained thickness 14 mm, weight 30,7 gram, 81,75 % moisture content, ash content 0,10 %, and 3,93 % crude fiber content, the concentration of 10 % obtained thickness 16 mm, weight 39,7 gram, 85,44% moisture content, ash content 0,11 %, and 4,5 % crude fiber content, the concentration of 20 % obtained thickness 15 mm, weight 32,5%, 82,65% moisture content, ash content 0,08 %, and 4,5 % crude fiber content.